2013
DOI: 10.1089/thy.2012.0033
|View full text |Cite
|
Sign up to set email alerts
|

The Mean Platelet Volume Is Positively Correlated with Serum Thyrotropin Concentrations in a Population of Healthy Subjects and Subjects with Unsuspected Subclinical Hypothyroidism

Abstract: The MPV was positively correlated with the TSH level. SCH is an independently associated factor with the highest tertile of MPV in a general Korean population. We propose that the MPV may contribute to the prothrombotic condition that is associated with SCH and perhaps even in putative euthyroid states where the TSH level is the higher part of the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 29 publications
3
29
4
1
Order By: Relevance
“…On the other hand, some researchers reported elevated MPV levels in hypothyroid patients (18). Large platelets with increased MPV values are active and release more thromboxane A2 than smaller ones, leading to an increased tendency to thrombosis (18). The absence of a significant difference in the MPV levels in the present study could be attributed to the different strategy of case selection.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…On the other hand, some researchers reported elevated MPV levels in hypothyroid patients (18). Large platelets with increased MPV values are active and release more thromboxane A2 than smaller ones, leading to an increased tendency to thrombosis (18). The absence of a significant difference in the MPV levels in the present study could be attributed to the different strategy of case selection.…”
Section: Discussioncontrasting
confidence: 62%
“…This finding is similar to that observed by Torun et al (27), who found no significant difference in MPV levels between overt hypothyroidism (10.2 fL) and subclinical hypothyroidism (9.4 fL) among nonobese women patients of reproductive age in Sanliurfa, Turkey. On the other hand, some researchers reported elevated MPV levels in hypothyroid patients (18). Large platelets with increased MPV values are active and release more thromboxane A2 than smaller ones, leading to an increased tendency to thrombosis (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations